Oxidized High-Density Lipoprotein Induces Endothelial Fibrosis Promoting Hyperpermeability, Hypotension, and Increased Mortality - Macarena Rojas; Yolanda Prado; Pablo Tapia; Leandro J. Carreño; Claudio Cabello-Verrugio; Felipe Simon (MDPI AG, 2022)
During systemic inflammation, reactive oxygen species (ROS) are generated in the bloodstream, producing large amounts of oxidized HDL (oxHDL). OxHDL loses the vascular protective features of native HDL, acquiring detrimental actions. Systemic inflammation promotes endothelial fibrosis, characterized by adhesion protein downregulation and fibrotic-specific gene upregulation, disrupting endothelial monolayer integrity. Severe systemic inflammatory conditions, as found in critically ill patients in the intensive care unit (ICU), exhibit endothelial hyperpermeability, hypotension, and organ hypoperfusion, promoting organ dysfunction and increased mortality. Because endothelial fibrosis disturbs the endothelium, it is proposed that it is the cellular and molecular origin of endothelial hyperpermeability and the subsequent deleterious consequences. However, whether oxHDL is involved in this process is unknown. The aim of this study was to investigate the fibrotic effect of oxHDL on the endothelium, to elucidate the underlying molecular and cellular mechanism, and to determine its effects on vascular permeability, blood pressure, and mortality. The results showed that oxHDL induces endothelial fibrosis through the LOX-1/NOX-2/ROS/NF-κB pathway, TGF-β secretion, and ALK-5/Smad activation. OxHDL-treated rats showed endothelial hyperpermeability, hypotension, and an enhanced risk of death and mortality, which was prevented using an ALK-5 inhibitor and antioxidant diet consumption. Additionally, the ICU patients showed fibrotic endothelial cells, and the resuscitation fluid volume administered correlated with the plasma oxHDL levels associated with an elevated risk of death and mortality. We conclude that oxHDL generates endothelial fibrosis, impacting blood pressure regulation and survival.